Diversitas Suku Agamidae (Reptilia: Squamata) pada Berbagai Tipe Habitat di Kawasan Pertambangan Emas Martabe, Sumatera Utara: Dalam Tahap Konstruksi - Awal Riyanto (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
A study of Agamid lizards diversity and their distribution surrounding Martabe Mining project Area, South Tapanuli, North Sumatera was conducted in five different habitat types. The data were gathered by opportunistic searching in each habitat type with two replications. Shannon-Wiener index was used to determine the diversity while the homogeneity was verified by Pielou index. The similarity of Agamid communities among habitat types was confirmed by Sorensen coefficient. As a result, 9 Agamid species were recorded with Draco melanopogon as the major component of Agamid community making up 49.1% of total individuals gathered. Highest diversity occurred in moderately disturbed forest, but the most homogeny took place in riparian lowland forest. The cluster analysis using Sorensen’s coefficient of agamid species distribution among habitat types distributed the habitats into three major groups, with the most similarity occurred between primary and riparian lowland forests (75%). The identification key of the species was made.